Methods of determining the economic effect - Zhang, Yi; Ponomarov, V. D.; Savchenko , O. I. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Determining the economic impact of a particular activity, project or investment is an important task in business management. This effect can be assessed using different methods depending on the nature of the activity and the purpose of the assessment. The report proposes the main methods for determining the economic effect and provides recommendations for their effective use.
Методи визначення економічного ефекту
Keywords: effect; effectiveness; determination methods; calculations; enterprises